234k views
1 vote
Simply (m^3np^-3)^3(mn^4p^2)

User HSLM
by
5.2k points

1 Answer

4 votes

Answer:


=(m^(10)n^7)/(p^7)

Explanation:


(m^3np^-^3)^3(mn^4p^2)\\\\\mathrm{Remove\:parentheses}:\quad \left(a\right)=a\\=\left(m^3np^(-3)\right)^3mn^4p^2\\\\\left(m^3np^(-3)\right)^3\quad :\quad m^9n^3p^(-9)\\\\=m^9n^3p^(-9)mn^4p^2\\\\\mathrm{Apply\:exponent\:rule}:\quad \:a^b*\:a^c=a^(b+c)\\\\m^9m=\:m^(9+1)\\\\=n^3p^(-9)m^(9+1)n^4p^2\\n^3n^4=\:n^(3+4)\\\\=n^3p^(-9)m^(10)n^4p^2\\\\\mathrm{Apply\:exponent\:rule}:\quad \:a^b*\:a^c=a^(b+c)\\=p^(-9)m^(10)n^(3+4)p^2\\\\=p^(-9)m^(10)n^7p^2\\\\=m^(10)n^7p^(-9+2)


=m^(10)n^7p^(-7)\\\\=m^(10)n^7(1)/(p^7)\\\\(1*\:m^(10)n^7)/(p^7)\\\\=(m^(10)n^7)/(p^7)

User Daggett
by
5.4k points